Protesting Retrospectively: Oral Memories and Social Practices of Migrants from the Areas of Artificial Water Reservoirs in Soviet Ukraine - Koval-Fuchylo, Iryna (FOLKLORICA - Journal of the Slavic, East European, and Eurasian Folklore Association, 2022)
Between the 1920s and the 1980s, Soviet Ukraine saw six large hydroelectric power plants constructed on the Dnipro River and one on the Dnister River. (1) The projects necessitated the creation of artificial water reservoirs, resulting in the destruction of a large number of old villages. The residents of these places were forcibly resettled. In the 1960s and 1970s, a time period that constitutes the main focus of this paper, the only form of protest to forcible resettlement was defiance: according to the state plan, while people were required to demolish their houses and build new ones in a specially designated place, many did not. Any other form of protest was dangerous in a totalitarian state. The weakening and further collapse of the Soviet regime altered the political climate, and Ukraine has since witnessed numerous expressions of discontent in the forms of strikes, rallies, collective statements, etc. These experiences led to a rethinking of the Soviet past and a search for protest where it previously had not existed. The present article focuses on narratives and social events that serve as creative responses to the forcible resettlement. It shows that these forms of protest have emerged as a result of changing perceptions of the feasibility of hydropower and an understanding of the losses caused by the flooding of forests, pastures, and farmlands. The present case study illustrates that protests, typically associated with immediate response to political events, can sometimes form retrospectively, and can be directly shaped by the processes of the formation and traditionalization of memory.